Integration of the Presentation of Educational Material in the Flipped Learning Model - L. M. Manakova (Высшее образование в России)
The article addresses the issue of integrating forms of educational material in flipped learning of the university students. Research ideas concur (and possibly develop) the thesis of conceptual changes in flipped learning stated in an article by I.I. Gnutova “From Flipped Classroom to Flipped Learning: Evolution of the Concept and Its Philosophical Foundations” (Vysshee obrazovanie v Rossii. Vol. 29, no. 3, pp. 86-95). The model of the flipped learning of the discipline involves the presentation of its content in four blocks, where the objectives and teaching methods are different. In order to ensure the establishment of associative links in the organization of mastering the content of these blocks, it is necessary to integrate the forms of educational material that are used in them. The main result of the study are: an effective way to integrate educational material in an flipped learning is the selection or creation of its forms, organizing the educational activities of students based on the logical analysis of the text in the textbook as the main means of learning. As a result, there is a new educational text as an original remix of the text from the textbook, which constitutes a multimedia learning environment for a specific topic.